Assessment of Sequelae of COVID-19 Nearly 1 Year After Diagnosis - Zhou, Fangyuan; Tao, Meihui; Shang, Luorui; Liu, Yuhan; Pan, Guangtao; Jin, Yan; Wang, Li; Hu, Shaoke; Li, Jinxiao; Zhang, Mengqi; Fu, Yu; Yang, Shenglan (Frontiers in Medicine, 2021)
Background: A previous study has shown that 81% of the COVID-19 patients had mild or moderate symptoms. However, most studies on the sequelae in COVID-19 patients focused on severe cases and the long-term follow-up studies on the health consequences in non-severe cases are limited. The current study aimed to assess the sequelae of COVID-19 in patients nearly 1 year after diagnosis with a particular focus on the recovery of patients with non-severe COVID-19. Methods: We enrolled 120 patients infected with SARS-CoV-2 discharged from Wuhan Union hospital west district (designated hospital for COVID-19) and Fangcang shelter hospitals between January 29, 2020 and April 1, 2020. All participants were asked to complete a series of questionnaires to assess their symptoms and quality of life and for psychological evaluation. Also, pulmonary function test, chest CT, 6-min walking test (6MWT), routine blood test, liver and kidney function tests, fasting blood glucose test, lipid test, and immunoglobulin G antibody test were performed to evaluate their health. Results: The mean age of the study population was 51.6 ± 10.8 years. Of the 120 patients, 104 (86.7%) were cases of non-severe COVID-19. The follow-up study was performed between November 23, 2020 and January 11, 2021, and the median time between the diagnosis and the follow-up was 314.5 (IQR, 296–338) days. Sleep difficulties, shortness of breath, fatigue, and joint pain were common symptoms observed during follow-up and nearly one-third of the non-severe cases had these symptoms. A total of 50 (41.7%) and 45 (37.5%) patients reported anxiety and depression, respectively. And 18.3% of the patients showed negative results in the IgG test at the follow-up, which correlated with the severity of the infection (R = 0.203, p = 0.026), and the proportion of IgG negative cases in non-severe COVID-19 patients was higher than that in the severe cases (20.2 vs. 6.3%). Pulmonary diffusion impairment was reported in 30 (26.1%) out of 115 patients, and 24 (24.2%) out of the 99 non-severe cases. The values of forced vital capacity (FVC), forced expiratory volume in 1 s (FEV1), FVC/FEV1, vital capacity (VC), total lung capacity (TLC), and residual volume (RV) were less than the normal range in 1.7, 8.6, 0.9, 11.2, 7.0, and 0.9% of the patients, respectively. A total of 55 (56.7%) out of the 97 patients showed abnormal CT findings, including ground-glass opacities (GGO), bronchiectasis, nodules, lines and bands, and fibrosis. Furthermore, there was a correlation between all the SF-36-domain scores and the duration of hospitalization, pulmonary function, and a 6MWT. Conclusions: At the nearly 1-year follow-up, COVID-19 survivors still had multi-system issues, including those in the respiratory functioning, radiography, quality of life, and anxiety and depression. Moreover, non-severe cases also showed some sequelae and the proportion of IgG negative cases in the non-severe patients was higher than that in severe cases. Therefore, conducting follow-ups and preventing the reinfection of SARS-CoV-2 in this group is necessary.